RESEPSI HADIS DALAM TRADISI SYAWALAN DI MASYARAKAT JAWA TENGAH - Susanti, Rini (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2023)
A religious tradition in society does not occur suddenly. The tradition is formed as a result of the process of transmission and transformation of understanding of religious texts, both from the verses of the Qur'an and the sayings of the Prophet. The role of local leaders in transmitting the interpretation of these texts is crucial. The reception of understanding from these local leaders is then followed by the surrounding community, thus becoming an inherited tradition. One of these inherited traditions is found in the Central Java community, specifically in the city of Pekalongan. The people of Pekalongan have a unique tradition called